Attempts to prime intellectual virtues for understanding of science: Failures to inspire intellectual effort. (17th November 2017) - Huxster, Joanna; Hopkins, Melissa; Bresticker, Julia; Leddington, Jason; Slater, Matthew
Abstract: Strategies for effectively communicating scientific findings to the public are an important and growing area of study. Recognizing that some complex subjects require recipients of information to take a more active role in constructing an understanding, we sought to determine whether it was possible to increase subjects' intellectual effort via "priming" methodologies. In particular, we asked whether subconsciously priming "intellectual virtues" (IVs), such as curiosity, perseverance, patience, and diligence might improve participants' effort and performance on various cognitive tasks. In the first experiment, we found no significant differences in either effort or understanding between IV-primed and neutrally-primed individuals across two different priming techniques. The second experiment measured the effect of IV-priming on intellectual effort in simpler, shorter-duration puzzles and exploration activities; here, we observed an effect, but given its low strength and short duration, we do not believe that priming of IVs is a promising strategy for science communication.